61-c=9

Simple and best practice solution for 61-c=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 61-c=9 equation:


Simplifying
61 + -1c = 9

Solving
61 + -1c = 9

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-61' to each side of the equation.
61 + -61 + -1c = 9 + -61

Combine like terms: 61 + -61 = 0
0 + -1c = 9 + -61
-1c = 9 + -61

Combine like terms: 9 + -61 = -52
-1c = -52

Divide each side by '-1'.
c = 52

Simplifying
c = 52

See similar equations:

| 3x^2-x^2+1600=0 | | 10(w+3)-14=66 | | 26=3(10.5+-0.25y)-2y | | -2(j-3)=-2j-6 | | 4w^2+21w-21=0 | | 6x-83=-47 | | 55(2x-1)=25 | | 4(y+5)=100 | | 273-7p=42 | | X+x+3+4= | | 58=-3n+-32 | | 0.3-7=11+0.2 | | 5x+4=7x-96 | | 4y+12+6y=24y-8+[-2y] | | 7v+6=5v+16 | | 5x+2y=117 | | 76=4x-8 | | 2x-10y+7=0 | | 35=11y+2 | | .5(6x-3)=.5(6+6x) | | -(7x+10)-10=-8(4+x) | | 2(c+6)=3G-6g | | x=3x-40 | | 7b=10b+18 | | 6(-10p-3)-8p=6(-12p-3)-4 | | v^2-4v-37=2 | | 24x-3(2x-5)=51 | | 73-x=86-2x | | (2x^2-3xy^2-y^2)-(3x^2-xy^2)= | | F(X)=20(0.9)x^6 | | 6m+9+7x-2= | | 9.25x=5.75x+40 |

Equations solver categories